Sensing atrazine herbicide degradation products through their interactions with humic substances by surface-enhanced raman scattering - Zanasi, Giulia (2021)
In this work, we have developed a simple method to carry out the quantitative analysis of deethylhydroxyatrazine (DEHA), the most abundant metabolite of atrazine herbicide (ATZ), based on the surface-enhanced Raman scattering technique. Since this ATZ product can undergo pH-dependent tautomerization, a previous characterization of the DEHA vibrational spectrum was accomplished. This study consisted of the Raman scattering study, both experimental and theoretical, of the enolic and ketonic tautomers of this molecule. SERS spectra were recorded at different pH in order to assess the effect of the metal surface in nanoparticles along with the pH on the structure of DEHA and to find the optimal experimental conditions of the quantitative detection of DEHA. Additionally, the interaction of DEHA with two types of humic acid reference standards, the Elliot humic and leonardite humic ones, was also performed by SERS. This interaction was conducted with two different objectives: to evaluate the interaction mechanism of the ATZ degradation product with humic substances and to check if this interaction can modify the sensitivity of the SERS detection of DEHA. The results presented in this study have clearly demonstrated that SERS spectroscopy is a very powerful technique for characterizing DEHA and other triazine sub-products at a very low concentration in water and also for analyzing the interaction of these important pollutants with humic substances.